2008
DOI: 10.3758/lb.36.3.174
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-pair training enhances transposition in pigeons

Abstract: 174For 7 decades, Kenneth W. Spence's (1937) theory of discrimination learning has provided an elegant and sometimes counterintuitive account of several important behavioral phenomena, including transposition, which was first explored by Köhler (1918Köhler ( /1938. In a typical transposition task, a subject may be given a single pair of simultaneously presented stimuli (e.g., a 3-cm circle and a 4-cm circle) and may be required to select the smaller one (the 3-cm circle). Originally, transposition was said to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 34 publications
4
45
0
Order By: Relevance
“…We therefore argue that the discrimination behavior of our crows is best explained by relational discriminations. Our result of relational discriminations in crows is in agreement with more recent findings in pigeons that -albeit for different experimental reasons -also showed behavior based on relational factors (Lazareva et al, 2005(Lazareva et al, , 2008Lazareva, 2012).…”
Section: Scope and Limit Of Relational Length Discriminationsupporting
confidence: 93%
“…We therefore argue that the discrimination behavior of our crows is best explained by relational discriminations. Our result of relational discriminations in crows is in agreement with more recent findings in pigeons that -albeit for different experimental reasons -also showed behavior based on relational factors (Lazareva et al, 2005(Lazareva et al, , 2008Lazareva, 2012).…”
Section: Scope and Limit Of Relational Length Discriminationsupporting
confidence: 93%
“…pigeons (Lazareva et al 2008;Lazareva et al 2005) have been found to master such an abstraction of absolute information to relative information. However, most studies used a single form of stimulus, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the level of generalization possessed by the gulls concerning the relative features we used two types of transfer tests: transfer to novel stimuli of the same category and transfer to novel stimuli of novel category (Wilson et al, 1985). The ability to transfer to stimuli of the same category (insignificantly differing from those used during training) is shown not only for large-brained representatives of a class of birds -crows and parrots (Koehler, 1956;Pepperberg, 1987Pepperberg, , 2000Wilson et al, 1985), but also for pigeons -birds with a low level of brain structure that have a Portmann Index (Portmann, 1947) the same as gulls, approximately corresponding to a four (Emery, 2006;Lazareva et al, 2008;Zentall et al, 2008;Wright & Delius, 2005). For example, pigeons trained to select coloured boxes by similarity, in the transfer tests successfully selected novel stimuli not used during the training (Katz & Wright, 2006).…”
Section: Discussionmentioning
confidence: 99%